Approaching Protein Barriers: Emerging Mechanisms of Replication Pausing in Eukaryotes - Shyian, Maksym; Shore, David (Frontiers in Cell and Developmental Biology, 2021)
During nuclear DNA replication multiprotein replisome machines have to jointly traverse and duplicate the total length of each chromosome during each cell cycle. At certain genomic locations replisomes encounter tight DNA-protein complexes and slow down. This fork pausing is an active process involving recognition of a protein barrier by the approaching replisome via an evolutionarily conserved Fork Pausing/Protection Complex (FPC). Action of the FPC protects forks from collapse at both programmed and accidental protein barriers, thus promoting genome integrity. In addition, FPC stimulates the DNA replication checkpoint and regulates topological transitions near the replication fork. Eukaryotic cells have been proposed to employ physiological programmed fork pausing for various purposes, such as maintaining copy number at repetitive loci, precluding replication-transcription encounters, regulating kinetochore assembly, or controlling gene conversion events during mating-type switching. Here we review the growing number of approaches used to study replication pausing in vivo and in vitro as well as the characterization of additional factors recently reported to modulate fork pausing in different systems. Specifically, we focus on the positive role of topoisomerases in fork pausing. We describe a model where replisome progression is inherently cautious, which ensures general preservation of fork stability and genome integrity but can also carry out specialized functions at certain loci. Furthermore, we highlight classical and novel outstanding questions in the field and propose venues for addressing them. Given how little is known about replisome pausing at protein barriers in human cells more studies are required to address how conserved these mechanisms are.